Exchanging natural enemies species of lepidopterous cereal stemborers between African regions - Schulthess, F.; Bosque Pérez, N.A.; Chabi-Olaye, A.; Gounou, S.; Ndemah, R.; Goergen, Georg E. (1997)
Difficulties of identification of natural enemies of cereal stemborers for 'redistribution' in Africa are discussed. Tritrophic level studies on wild and cultivated habitats of borers and beneficial species are needed to judge the impact of a natural enemy species in the cropping system. Areas witli low Pest pressure which are climatically favorable for Pest development may be selected for study. Based on the results of various countrywide surveys to map the relative importance of Sesaniia calnmistis Hampson, Eldam sncc@rim (Walker) and Busseola fuscn (Fuller) in western Africa, recommendations are given for sites for tritrophic level studies. It is hypothesised that because maize is not always present in the field and because of its high susceptibility, natural biological control has to come I'rom wild habitats. This emphasises the importance of the knowledge on the wild host-plant range. Survey results complemented with oviposition and life-table studies in the laboratory showed that, ratlier than being reservoirs for pests, most wild grass species act as trap plants causing mortalities of 100%. A comparison of light trap catches with pupae found on wild hosts and the scarcity of known wild hosts in areas with high Pest pressure suggest gaps in Our knowledge of the range of host plant species. Based on comparison of known natural enemy complexes in East and West Africa, the scelionid egg parasitoid Teleriorrius isis and an East African strain of the braconid larval parasitoid Cotesia sesainine (Cameron) are proposed for redistribution against B. fuscn and S. calaniis fis, respectively. Telenonius isis has never been reported from East Africa whereas C. sesaniiae is common in East and southern Africa and scarce in western Africa, suggesting that C. sesaniiae is probably not adapted to S. culnmistis and B.fiisca in this region.